Biodiesel Production from Rubber Seed Oil as An Alternative Energy Source – A Review - Herawati Budiastuti; Nira Aulia Hanifah; Devita Utami Mardiani; Haryadi Haryadi; Rusdianasari Rusdianasari; Ahmad Fudholi (Bandung State Polytechnic (Politeknik Negeri Bandung), 2022)
Biodiesel is one of alternative energies that can be used to overcome problem caused by limited amount of fossil fuels reserved. Biodiesel can be made from rubber seed oil that has high potencies in Indonesia. The availability of rubber seed is quite much with more than 3-million-hectare rubber plantation area. The production of biodiesel from rubber seed oil has been carried out by several researchers using various methods. Therefore, this study was conducted as a review to obtain optimum operation conditions and effect of antioxidant addition in biodiesel production. Production methods of biodiesel from rubber seed oil observed in this study are esterification-transesterification, one stage transesterification, and in situ transesterification methods. Types of antioxidant added to biodiesel from rubber seed oil observed are TBHQ, D-TBHQ, BHA, BHT, PG, and OG. Esterification-transesterification was chosen as the most effective method in producing biodiesel with a minimum yield of 96.4%. Antioxidant addition of TBHQ with 1000 × 10-6 (ω) dosage was selected as the most effective to increase biodiesel induction period to become 6.41 hours, fulfilling the SNI 7182-2015 standard, which is minimum of 6 hours. Standard used as the reference for observing biodiesel parameters is SNI 7182-2015.